Lama Menyusui Dan Tingkat Kemiskinan Keluarga Kaitannya Dengan Kejadian Stunting Pada Anak Balita : Studi Literatur - Lusyana Gloria Doloksaribu; Efendi S Nainggolan; Tiurlan Mariasima Doloksaribu (NUTRIENT, 2022)
Background Stunting is one of the nutritional problems faced in today's world that many toddlers experience. Stunting is a condition where children under five have a length / height that is less when compared to age. The incidence of stunting arises from conditions such as poverty and inappropriate breastfeeding. The aim of the study was to determine the relationship between length of breastfeeding and the level of family poverty with the incidence of stunting in children under five in a literature study. The type of research used is a literature study with secondary data collection from scientific research articles from 2015-2020. Article selection is done by setting inclusion and exclusion criteria consisting of duplication, title, abstract and PICOS criteria. Search data using the online Google Scholar, DOAJ, PubMed and Garuda databases using the key words "long breastfeeding" AND toddler stunting, and family poverty level AND "toddler stunting". The articles obtained were 289 articles, but only 11 articles that matched the inclusion criteria. Selected articles are then evaluated. The results of this literature study found that 5 out of 11 articles that examined the relationship between poverty and stunting showed that 100% of the articles stated that there was a relationship. Children from poor families tend not to get good nutrition because they cannot provide food at the household level. . Likewise with the length of breastfeeding. 6 out of 11 articles that reviewed this subject, 100% showed that there was a relationship between the length of breastfeeding and the risk of stunting. The longer breastfeeding is given, the less stunting occurs. In conclusion, The family poverty rate and the length of breastfeeding are related to the incidence of stunting in children under five